A systematic review of the factors contributing to adolescent illicit drug use within Asia - Tang, Sui Sum; Hamsan, Hanina H.; Ma'rof, Aini Azeqa; Abdullah, Haslinda; Mohd Rasdi, Roziah; Omar, Siti Zobidah; Sadiron, Nazira (Human Resource Management Academic Research Society, 2022)
Adolescents are particularly vulnerable to illicit drug use, and substance use among adolescents is a worldwide health issue. Scholars have conducted many empirical studies to identify the causes of addiction, prevention, and intervention to reduce adolescent involvement in substance use and prevent substance abuse later in adulthood. Despite the significant result in determining risk and protective factors in western society, the relative success of the domain of risk and protective factors towards substance use has not been well-documented within Asia. Hence, this systematic review article examines the risk and protection factors for illicit drug use among adolescents in Asia. Preferred reporting items for Systematic Reviews and Meta-Analyses (PRISMA) to present a systematic literature review of 13 out of 363 articles from four databases (Scopus, Science Direct, Google Scholar and Dimension). The study's findings identified three main themes: individual level, interpersonal level, and institutional level. Overall, further analysis established eight sub-themes. Adolescents' individual level is most highlighted in this study. However, multiple factors within a different level, such as interpersonal, community and policy, are essential to further explore and develop effective substance abuse prevention strategies.